2D Amorphous Mo‐Doped CoB for Bidirectional Sulfur Catalysis in Lithium Sulfur Batteries. (6th May 2022) - Feng, Tao; Zhao, Teng; Zhang, Nanxiang; Duan, Yuzhen; Li, Li; Wu, Feng; Chen, Renjie
Abstract: The amorphous metal boride materials are attractive catalyst for advanced lithium sulfur batteries, but their catalytic mechanism remains unclear. Herein, 2D amorphous Mo‐doped cobalt boride (Co7 Mo3 B) is designed for the first time as bidirectional sulfur catalysis by rapid chemical reduction. The atom cluster structure of Co7 Mo3 B is revealed by theoretical calculation. Electron paramagnetic resonance test further confirms that Co7 Mo3 B has interstitial compound structure characteristics. Experimental results show that the porous 2D nanosheets structure and the interaction of Mo, B, Co atoms contribute to enhanced conductivity, high long‐chain lithium polysulfides affinity, and reversible Li2 S nucleation and dissociation, thus accelerating LiPSs reduction and Li2 S oxidation kinetics. In addition, the interstitial Co7 Mo3 B enables intercalation of Li and B during charging–discharging while keeping the structure stable. As a result, the S cathode with Co7 Mo3 B catalyst delivers good life (1000 cycles at 5 C), superior rate performance (10 C). Even at high sulfur areal loading of 6.79 mg cm –2 and electrolyte/sulfur ratio of 5 μL mg –1, the Co7 Mo3 B/S composite cathode still exhibits good areal capacity and capacity retention rate. Abstract : An efficient Mo‐doping cobalt boride amorphous catalyst (Co7 Mo3 B) is designed for lithium‐sulfur batteries. It exhibits an outstanding electrocatalytic effect on lithium polysulfides conversion by integrating experimental data and density functional theory calculations. The interstitial compound structure and mechanism of Co7 Mo3 B have been explored during the charging–discharging process. The cells with Co7 Mo3 B/S display excellent cycling life and superior rate performance.